Genome Editing in Neuroepithelial Stem Cells to Generate Human Neurons with High Adenosine‐Releasing Capacity. (28th March 2018) - Poppe, Daniel; Doerr, Jonas; Schneider, Marion; Wilkens, Ruven; Steinbeck, Julius A.; Ladewig, Julia; Tam, Allison; Paschon, David E.; Gregory, Philip D.; Reik, Andreas; Müller, Christa E.; Koch, Philipp; et al.
Abstract: As a powerful regulator of cellular homeostasis and metabolism, adenosine is involved in diverse neurological processes including pain, cognition, and memory. Altered adenosine homeostasis has also been associated with several diseases such as depression, schizophrenia, or epilepsy. Based on its protective properties, adenosine has been considered as a potential therapeutic agent for various brain disorders. Since systemic application of adenosine is hampered by serious side effects such as vasodilatation and cardiac suppression, recent studies aim at improving local delivery by depots, pumps, or cell‐based applications. Here, we report on the characterization of adenosine‐releasing human embryonic stem cell‐derived neuroepithelial stem cells (long‐term self‐renewing neuroepithelial stem [lt‐NES] cells) generated by zinc finger nuclease (ZFN)‐mediated knockout of the adenosine kinase (ADK) gene. ADK‐deficient lt‐NES cells and their differentiated neuronal and astroglial progeny exhibit substantially elevated release of adenosine compared to control cells. Importantly, extensive adenosine release could be triggered by excitation of differentiated neuronal cultures, suggesting a potential activity‐dependent regulation of adenosine supply. Thus, ZFN‐modified neural stem cells might serve as a useful vehicle for the activity‐dependent local therapeutic delivery of adenosine into the central nervous system.Stem Cells Translational Medicine 2018;7:477–486 Abstract : Site‐specific disruption of adenosine kinase results in the augmented release of adenosine into the extracellular space. The amount of secreted adenosine increases during differentiation of neuroepithelial stem cells into neurons and is even further enhanced upon excitatory stimulation. Such an engineered cell population could release neurosuppressive adenosine on demand when high neuronal activity is present, for example in epilepsy.